Some Aspects of Domestic Violence in the Gender Approach - MICHAILOVIČ, ILONA (Kriminologijos studijos, 2014)
[full article and abstract in Lithuanian; abstract in English]Criminal justice can only respond to evidenced results of domestic violence, being unable to reduce it. It is only possible to expect stable changes in cooperation through many areas influencing changes of people’s behaviour, including education, social policy, and culture. The analysis of legal protection against domestic violence contributes by highlighting the existing issues the emphasis on which helps to eliminate them. By researching the violent criminal offenses in modern victimology, it should be noted that there are crimes whose victims are women, including the criminal offenses related to domestic violence. Of course, the degree of a women becoming a victim of a crime depends on the particular culture of society and permits for aggression in society. However, thanks to the wide approach to the domestic violence topic treatment, there are increasing cases of women making offenses in their close environment. In accordance with the decisions of the European Court of Human Rights (ECHR) related to the topics of domestic violence, we can say that one of the main values should be the effectiveness of state regulations and actions resisting domestic violence. Otherwise, the violence in daily life may lead to state government responsibility to the ECHR. We can only hope that there will be more ECHR cases concerning domestic violence; thus, the decisions of this Court will affect the national law. The provisions of the Council of Europe Convention on preventing and combating violence against women and domestic violence should also be of high value.
Keywords: domestic violence; victimological point of view; gender approach